(untitled) (Indian Journal of Animal Production and Management, 2024)
The rapidly growing global human population, currently at 8 billion (UN, 2022), poses significant challenges to food and nutritional security. Livestock, especially dairy production, has the potential to play a transformative role in addressing these challenges by converting low value, inedible resources into essential animal source foods such as milk, meat, and eggs. Despite ongoing efforts to enhance productivity in this sector, there are growing concerns about the ethical implications, particularly regarding animal welfare. The rising consumer awareness and changing attitudes toward the treatment of farm animals have made animal welfare a crucial factor in modern dairy farming. The welfare of dairy animals is not only a matter of ethical concern but is also closely linked to the efficiency of production systems and the quality of the end products. In the Indian context, where dairy cattle hold both economic and cultural significance, the reality often contrasts with the ideal, as evidenced by the high number of stray cattle and compromised animal welfare. Addressing these challenges is essential for the sustainability of dairy farming, and this can be achieved through the integration of welfare-oriented management practices. Such practices include proper feeding, breeding, housing, health management, and humane handling during transportation. By adopting these strategies, which also align with changing consumer preferences, dairy farming can become more sustainable and economically viable, benefiting both animals and farmers.